Resiliência familiar: fatores de risco e de proteção em mães de filhos com paralisia cerebral - Silva, Cristina Maria Brilhante da (2013)
Resilience can beunderstood as a dynamic process involving a positive adjustment despite of the circumstances of significant adversity. Though, when it comes to families that have children with cerebral palsy, the resilience process is a reality for the mothers interviewed in this research. However, the family s resilience phenomenon is a context that requires investigation from a conceptual and methodological point of view. This paper presents and discusses the coping, possibilities and adversities within the family circle. A notion of applied resilience in Psychology was taken as a basis. Thus, the goal of this study is to spot the resilience strategies of six mothers of kids with cerebral palsy among the numberless risk factors. For this, a qualitative research was employed, so that an action-research was used as an intervention, and the data collection was done by a focus group technique, being performed at APAE in Anápolis-GO. The development was guided by theoretical of the family resilience phenomena grounded in family beliefs of Walsh (2005). During the investigation a systematic chart of resilience process in mothers was obtained, which provides arrow indicators for coping strategies to other mothers in similar situations. From these charts, illustrative charts were elaborate which allowed presenting a general perspective of the attendant s speeches brought up in the focus group. They also made it possible to visualize the mother s common trajectory efficiently and positively. In general, the obtained data emphasizes the coping strategies, the beliefs expressed, in which the most presented were: sense of coherence and meaning, self faith and faith in God; active initiative and shared responsibility. Also, the undertaken actions that happened through the search of specialized treatment to people with cerebral palsy; the pursuit of rights and benefits were also found; furthermore, protection factors such as: APAE; PSF; friend and neighborhood were detected. Although, the results presented, there are others, such as: interaction nature that focused the backing: emotional, material, of information and evaluation. And finally, the other results presented were BPC admission, child s enrollment at APAE; neighbors start to help and specialized care acquisition. In conclusion, family resilience is real and has a lot to contribute and teach not only the families with disabled members, but also any family that faces this conflict regardless its nature. Therefore, the results awake the notion focus groups play a role as an indicator of protection in the family resilience demonstration.(Appendix I).